Formation of oxysterols during thermal processing and frozen storage of cooked minced meat - Sabolová, Monika; Pohořelá, Barbora; Fišnar, Jakub; Kouřimská, Lenka; Chrpová, Diana; Pánek, Jan (Journal of the science of food and agriculture, 2017)
BACKGROUND: Cholesterol is susceptible to oxidation and the formation of oxysterols, which could have a negative health effect. The formation and distribution of oxysterols was investigated in meatloaves prepared under different baking regimes with an increased temperature or prolonged time. The effect of frozen storage and marjoram addition on the level of oxysterols was also investigated. RESULTS: The effect of baking regime on the content and distribution of oxysterols was determined. Temperature was the most important factor affecting 7-ketocholesterol formation in baked meatloaf. Its content was significantly higher after baking at 250 °C compared to at 180 °C. The content of 7-ketocholesterol increased from the centre (87 µg kg-1 ) to the surface (122 µg kg-1 ) of baked meatloaves prepared under standard conditions. The level of α-tocopherol and its distribution was also affected by the baking regime. A higher level of 7-ketocholesterol was found in baked meatloaves after their frozen storage. The addition of marjoram did not change this level. CONCLUSION: Inadequate culinary conditions used for preparation of baked meat can contribute to an increased oxysterol intake in the diet. Frozen storage did not stop oxysterol formation. The inhibition effect of marjoram on sterols oxidation was not confirmed. © 2017 Society of Chemical Industry.
Keywords: skot; Oxysterols; oxysteroly; maso; zmrazování; vaření; baking; meat products; vysoká teplota; Freezing; cholesterol; Animals; prasata; zvířata; lipid oxidation; skladování potravin; Hot Temperature; Cooking; Cattle; Meat; nutritional aspects; Swine; Food Storage